Students' Perception in Learning Mathematics Using Quizizz - Winarsih, Sri; Nur komalasari; Anggita Maharani; Muchammad Subali Noto (PT Inovasi Pratama Internasional, 2024)
Mathematics is a subject that has its challenges. This challenge is related to the negative perception of mathematics learning, which is considered complex and saturated. Quizizz is one of the defense media that is considered exciting and fun. This study aims to determine the perception of Madrasah Aliyah (MA) students towards mathematics learning using the Quizizz application. The research method used in this study is quantitative descriptive using a questionnaire consisting of 30 statements. The respondents to this study are 30 MA Al Zaytun Indramayu students who have used Quizizz in mathematics learning in the even semester of the 2023-2024 Academic Year. The study results show that the use of Quizizz in mathematics learning, in general, can be positively received by students. Students feel more motivated to learn, engage, and understand the material better when using the Quizizz app. However, there are several challenges, such as difficulties in understanding the material and time pressure in working on problems some students feel. Overall, Quizizz is considered an effective tool for improving students' learning outcomes and interest in math, with the note that its implementation should be tailored to the needs of students.